Immigration and trade with East Asia in the food industry : the contribution of immigrants - Rod Tess 1948 (Canberra, A.C.T. : Australian Govt. Pub. Service, 1995)
The study reviews the contribution of immigrants to Australian trade, with East Asia, in the food industry. The study focuses on whether there is any link between export success and the employment of people with the language and cultural skills corresponding to the export markets.
"Bureau of Immigration, Multicultural and Population Research"-Cover.
Bibliography: p. 84-88.
Keywords: Food industry and trade -- Australian investments -- Commerce -- With East Asia -- Australia -- East Asia